Antigenicity is preserved with fixative solutions used in human gross anatomy: A mice brain immunohistochemistry study - Frigon, Eve-Marie; Dadar, Mahsa; Boire, Denis; Maranzano, Josefina (Frontiers in Neuroanatomy, 2022)
Background Histology remains the gold-standard to assess human brain biology, so ex vivo studies using tissue from brain banks are standard practice in neuroscientific research. However, a larger number of specimens could be obtained from gross anatomy laboratories. These specimens are fixed with solutions appropriate for dissections, but whether they also preserve brain tissue antigenicity is unclear. Therefore, we perfused mice brains with solutions used for human body preservation to assess and compare the tissue quality and antigenicity of the main cell populations. Materials and methods Twenty-eight C57BL/6J mice were perfused with 4% formaldehyde (FAS, N = 9), salt-saturated solution (SSS, N = 9), and alcohol solution (AS, N = 10). The brains were cut into 40 μm sections for antigenicity analysis and were assessed by immunohistochemistry of four antigens: neuronal nuclei (NeuN), glial fibrillary acidic protein (GFAP astrocytes), ionized calcium-binding adaptor molecule 1 (Iba1-microglia), and myelin proteolipid protein (PLP). We compared the fixatives according to multiple variables: perfusion quality, ease of manipulation, tissue quality, immunohistochemistry quality, and antigenicity preservation. Results The perfusion quality was better using FAS and worse using AS. The manipulation was very poor in SSS brains. FAS- and AS-fixed brains showed higher tissue and immunohistochemistry quality than the SSS brains. All antigens were readily observed in every specimen, regardless of the fixative solution. Conclusion Solutions designed to preserve specimens for human gross anatomy dissections also preserve tissue antigenicity in different brain cells. This offers opportunities for the use of human brains fixed in gross anatomy laboratories to assess normal or pathological conditions.